FREQUENCY OF PSEUDO-EXFOLIATIVE GLAUCOMA OCCURRENCE - Bezkorovayna, І.М.; Nakonechnyi, D.O.; Жуіні Дхіа Еддін,; Zaludyak, O.M.; Gorlachova, P.M. (World of Medicine and Biology, 2019)
Study of ganglion cells is important in the early diagnosis of glaucoma. In our opinion, this is also true for PEG as one of the primary diagnostic procedures. The purpose of the study was to analyze the incidence of PEG in patients with PES, by studying the ganglion complex of the retina.Out of the total number of the surveyed patients with PES, it was found that 28% (n = 39) have elevated intraocular pressure. In 26% (n = 36) PEG was confirmed by the thinning of the NFL layer (38.2 ± 3.03), the GCL + IPL layers (55.4 ± 3.89), and also the NFL + GCL + IPL (93.75 ± 3.25). The frequency of PEG on the background of PES was 26% in our study. The GCS study (NFL + GCL + IPL) with indicators of 93.75 ± 3.25 is a diagnostic criterion for establishing the diagnosis of PEG.
Keywords: pseudo-exfoliative syndrome; pseudo-exfoliative glaucoma